Nexus between Telecommunications FDI and Economic Growth: Evidence from Nigeria (2008 – 2018) - Olubunmi, Solomon; Sunday, Apeh Ajene; Okpachu, Emmanuel (NIU Journal of Humanities, 2021)
This research work studied the impact of Telecommunications Sector Foreign Direct Investment on the Performance of the Nigerian Economy. It focuses on the role played by the flow of Foreign Direct Investment (FDI) by the Telecommunications sector of Nigeria on the growth of the economy. The Error Correction Mechanism (ECM) econometric method was used to examine the regression model. The results of the empirical analysis showed that Foreign Direct Investment has contributed significantly to the performance of the Telecommunications Sector in terms of its contribution to the Gross Domestic Product of Nigeria. Some of the recommendations made in the research project are that: the government should initiate policies that will promote the long-run growth of the Telecommunications sector and the economy at large; infrastructural facilities such as power supply should be efficiently provided; government should focus on maintaining political stability which should serve as key to sustainable growth and development of the telecommunications sector of the Nigerian economy etc. Keywords: Telecommunications, Economic Growth, Foreign Direct Investment, GDP, Error Correction Model.